What is the relationship between long working hours, over-employment, under-employment and the subjective well-being of workers? Longitudinal evidence from the UK. (September 2015) - Angrave, David; Charlwood, Andy
Are long working hours, over-employment and under-employment associated with a reduction in subjective well-being? If they are, is the association long or short-lasting? This article answers these questions through within-person analysis of a nationally representative longitudinal survey from the United Kingdom. The results suggest that long working hours do not directly affect subjective well-being, but in line with theories of person–environment fit, both over-employment and under-employment are associated with lower subjective well-being. However, over-employment is more likely for those who work the longest hours. The duration of the subjective well-being penalty associated with over-employment and under-employment is typically short, but subjective well-being levels tend to remain depressed for those who remain over-employed for two years or more. Results imply that state and organizational policies that reduce the incidence of long hours working are likely to enhance aggregate well-being levels.